ACR (AUTOMATIC CONTROL ROBOT) BERBASIS ATMEGA 8535 SEBAGAI APLIKASI MODEL ROBOT MENGGUNAKAN REL - Setiawan, Arif; Subali, Subali (Vocational School Diponegoro University, 2013)
Arif Setiawan, Subali, in this paper explain that a fixed rail track used as a railway line. Application of rail as a direct path not only to train. However, there are also robots that use rail movement path. Rail crossings are used as the robot is not made of steel, but a line. This robot uses a single rail line is black with a white stripe background of a width adapted to the sensor mounted on the robot. Photodiode sensor lines will be detected, and then transmitted to the microcontroller 8535 as the brain or the source of the instruction that has been programmed. 8535 will detect the sensor output and then process the data received to proceed to the Driver that is connected to the DC motor. The output of the microcontroller 8535 will also be displayed through the LCD as the display position of the sensor and input characters. As an added speed control robot 4x1 keypad which will give instruction in the form of characters into the Microcontroller. Keywords: Rail, Sensor Photodiode, Microcontroller 8535, DC Motor Driver, LCD, Keypad, DC Motor.